Anemia Screening and Health Education on Stunting Reduction Efforts - Nathalie Elischeva Kailola; Theresia Natalia Seimahuira; Rifah Zafarani Soumena; Presli Glovrig Siahaya (Unram Journal of Community Service, 2025)
Stunting and anemia remain major public health problems in Indonesia, particularly in Maluku Province, where prevalence rates continue to exceed national targets. This community service program aimed to reduce the risk of stunting by integrating anemia screening with maternal health education in Dullah Laut and Tamadan Villages, Tual City. The program was implemented over three days and consisted of counseling sessions on nutrition, hygiene, and dietary practices; anemia screening; general health checks; and the distribution of vitamins to toddlers. Screening results showed that in Dullah Laut Village, only 21 children demonstrated good nutritional status, while 18 were categorized as poor, very poor, or bad. By contrast, in Tamadan Village, 35 children were in good nutritional condition, with only two classified as poor. Counseling activities engaged 57 mothers in Wab Village and 64 mothers in Debut Village, focusing on clean and healthy living behavior, worm infestation, anemia prevention, and toddler nutrition. These findings highlight the urgent need for targeted, community-based interventions to address nutritional challenges, particularly in areas with high poverty, sanitation problems, and limited parental knowledge. The integration of screening and health education through Posyandu proved to be an effective approach for enhancing maternal awareness and supporting early detection of anemia, with the potential to contribute to stunting reduction efforts in Southeast Maluku.